Inspiratory Muscle Training and Its Impact on Weaning Success in Mechanically Ventilated ICU Patients: A Systematic Review - José Luís Alonso-Pérez; Víctor Riquelme-Aguado; Daniel Rodríguez-Prieto; Alejandro López-Mejías; Carlos Romero-Morales; Giacomo Rossettini; Jorge Hugo Villafañe (Journal of Functional Morphology and Kinesiology)
Background/Objectives: A major importance is now accorded to respiratory muscle weakness resulting from exposure to invasive mechanical ventilation (IMV) in intensive care unit patients. Some authors suggested that Inspiratory Muscle Training (IMT) could increase the chances of weaning off IMV. This systematic review examined the efficacy of IMT on weaning success in mechanically ventilated patients. Methods: A literature search was conducted on PubMed, Cochrane, and PEDro until June 2023. Weaning success, maximum inspiratory pressure (MIP), and Rapid Shallow Breathing Index (RSBI) were the outcome measures included. Results: Seven randomized controlled trials, including 517 participants under IMV for at least 48 h, were included in the review. From a qualitative point of view, a significant increase in MIP and a significant decrease in RSBI were found in the intervention group during the analysis. However, weaning success was the same between the intervention and control groups. No significant association was found between weaning success and the increase of MIP or the decrease of RSBI. Furthermore, it could not be demonstrated that a positive change in MIP or RSBI would increase the weaning success rates. Conclusions: From a qualitative point of view, IMT is effective in increasing MIP and decreasing RSBI. However, IMT has no significant impact on weaning success. Further research is recommended to analyze the effect of IMT on weaning success.